Genetic diversity among and within cultured cyanobionts of diverse species of Azolla - Sood, A; Prasanna, R; Prasanna, B M; Singh, P K (Folia microbiologica, 2008)
The cyanobionts isolated from 10 Azolla accessions belonging to 6 species (Azolla mexicana, A. microphylla, A. rubra, A. caroliniana, A. filiculoides, A. pinnata) were cultured under laboratory conditions and analyzed on the basis of whole cell protein profiles and molecular marker dataset generated using repeat sequence primers (STRR(mod) and HipTG). The biochemical and molecular marker profiles of the cyanobionts were compared with those of the free-living cyanobacteria and symbiotic Nostoc strains from Anthoceros sp., Cycas sp. and Gunnera monoika. Cluster analysis revealed the genetic diversity among the selected strains, and identified 3 distinct clusters. Group 1 included cyanobionts from all the 10 accessions of Azolla, group 2 comprised all the symbiotic Nostoc strains, while group 3 included the free-living cyanobacteria belonging to the genera Nostoc and Anabaena. The interrelationships among the Azolla cyanobionts were further revealed by principal component analysis. Cyanobionts from A. caroliniana-A. microphylla grouped together while cyanobionts associated with A. mexicana-A. filiculoides along with A. pinnata formed another group. A. rubra cyanobionts had intermediate relationship with both the subgroups. This is the first study analyzing the diversity existing among the cultured cyanobionts of diverse Azolla species through the use of biochemical and molecular profiles and also the genetic distinctness of these free-living cyanobionts as compared to cyanobacterial strains of the genera Anabaena and Nostoc.
Keywords: kapradiny; sinice; bakteriální proteiny; Bacterial Proteins; Culture Techniques; Molecular Sequence Data; fylogeneze; symbióza; Cyanobacteria; Symbiosis; Ferns; genetická variace; kultivační techniky; molekulární sekvence - údaje; Genetic Variation; Phylogeny